SWBNet: A Stable White Balance Network for sRGB Images - Li, Chunxiao; Kang, Xuejing; Zhang, Zhifeng; Ming, Anlong (Proceedings of the AAAI Conference on Artificial Intelligence, 2023)
The white balance methods for sRGB images (sRGB-WB) aim to directly remove their color temperature shifts. Despite achieving promising white balance (WB) performance, the existing methods suffer from WB instability, i.e., their results are inconsistent for images with different color temperatures. We propose a stable white balance network (SWBNet) to alleviate this problem. It learns the color temperature-insensitive features to generate white-balanced images, resulting in consistent WB results. Specifically, the color temperatureinsensitive features are learned by implicitly suppressing lowfrequency information sensitive to color temperatures. Then, a color temperature contrastive loss is introduced to facilitate the most information shared among features of the same scene and different color temperatures. This way, features from the same scene are more insensitive to color temperatures regardless of the inputs. We also present a color temperature sensitivity-oriented transformer that globally perceives multiple color temperature shifts within an image and corrects them by different weights. It helps to improve the accuracy of stabilized SWBNet, especially for multiillumination sRGB images. Experiments indicate that our SWBNet achieves stable and remarkable WB performance.